Application of the Locking Compression Pediatric Hip Plate™ in children with proximal femoral tumors - Jiang, Xin (Journal of orthopaedic surgery and research, 2022)
Pediatric proximal femoral tumors often present with accumulative and severe bone destruction and are often complicated by pathological fractures and malunion. Such tumors are treated clinically by lesion scraping and graft reconstruction with autologous iliac bone alone or in combination with artificial bone. This study aimed to determine the efficacy of the Locking Compression Pediatric Hip Plate™ in treating pediatric proximal femoral tumors. From 2012-2017, the Locking Compression Pediatric Hip Plate™ was applied for internal fixation in 28 children in the Department of Pediatric Surgery. The complications were pathological fractures in 19 patients and multiple lesions in 5 patients. Tumors were removed by tumor curettage and reconstruction with autogenous iliac bone or artificial bone graft. The Locking Compression Pediatric Hip Plate™ was then applied. Postoperative pathological examination confirmed the diagnosis. The cohort comprised 20 males and 8 females (mean age 7.8 ± 2.9 years). The mean follow-up duration was 26.1 ± 8.1 months (range 18-48 months). Post-treatment radiography showed that the lesions and local pathological fractures were healed in 3.2 ± 0.4 months (range 3-4 months), with no complications. Four patients continued to receive antineoplastic therapy postoperatively. Four patients experienced recurrence in situ, while another four developed distant metastases. The radiographic and joint function findings indicated that the affected limbs had excellent function. The mean Enneking score was 28.7 ± 1.0 points (range 27-30 points). Internal fixation with the Locking Compression Pediatric Hip Plate™ in children achieves good therapeutic effects. Moreover, the Locking Compression Pediatric Hip Plate™ resolves the shortcomings of external fixation by traditional plaster casts and internal fixation by Kirschner wires and elastic intramedullary screws.